MISSIO DEI AS A FOUNDATIONAL ONTOLOGICAL REALITY OF THE CHURCH - Gotopo, Jean Paul (Sekolah Tinggi Teologi Berea, Salatiga, 2025)
This study examines the concept of the Missio Dei as an important ontological element underlying the identity and existence of the Church. Using a qualitative methodology that combines theological analysis, biblical interpretation, and a comprehensive literature review, this research highlights how God's mission is not merely an additional activity but constitutes the very essence of the Church's existence. From a Protestant and Pentecostal perspective, this study highlights that the integration of Missio Dei into ecclesiastical structures fosters a dynamic and transformative approach to liturgical expression and social engagement. The findings suggest that as the Church internalizes its mission as an existential mandate, it becomes more innovative and responsive to contemporary cultural and social challenges, while simultaneously preserving its underlying theological principles. By internalizing its mission as an existential mandate, the Church becomes more innovative and responsive to contemporary cultural and social challenges while preserving its foundational theological principles. Consequently, this study provides significant insights for pastoral strategy development, offering practical recommendations to enhance the Church’s role as an agent of transformation in contemporary society.